Pediatric Respiratory Viral Infection - Stacy L. S. Yam; Joan Marie Javillo Baguio; Renee W. Y. Chan (Viruses, 2024)
Reflecting on this Special Issue dedicated to pediatric respiratory viruses, it is evident that the shadow cast by the global SARS-CoV-2 pandemic has profoundly impacted individuals of all ages and backgrounds, neonates and school-aged children being vulnerable cohorts resulting from the evolving immunological profiles and limited exposures to immunity-building experienced during this unprecedented era [...]